Cover Feature: Laccase‐Catalyzed Synthesis of Low‐Molecular‐Weight Lignin‐Like Oligomers and their Application as UV‐Blocking Materials (Chem. Asian J. 3/2018). Issue 3 (18th January 2018) - Lim, Jieyan; Sana, Barindra; Krishnan, Ranganathan; Seayad, Jayasree; Ghadessy, Farid J.; Jana, Satyasankar; Ramalingam, Balamurugan
Abstract : The Cover Feature illustrates a laccase‐catalyzed oligomerization of guaiacol and its analogues, utilizing oxygen as an oxidant, with a representative mode of chain growth by dehydrogenative C−C coupling. The promising UV blocking characteristics of the oligomers is represented as an umbrella blocking the UV rays from the sun. The UV spectra show the differences in the absorption behavior of monomeric vanillyl alcohol and its oligomer. The natural or bio‐derived oligomers could be sustainable alternatives to conventional synthetic UV stabilizers and attractive to coating, food packaging, and sunscreen industries. These oligomeric UV blockers are less vulnerable to leaching from formulated polymers or plastics owing to their larger size. More information can be found in the Full Paper by Balamurugan Ramalingam, Satyasankar Jana et al. onpage 284 in Issue 3, 2018 (DOI:10.1002/asia.201701573 ).